Inside/Outside Somalia - Liisa Laakso (Nordic Journal of African Studies, 2011)
The contextualization of Somali diaspora studies requires an understanding of the international dynamics of the conflict and its effects. For the international community trying to restrain Islamization on the one hand and warlordism on the other, it has been convenient to limit state power in Somalia. As a consequence, non-state actors and international organizations have a major role in the implementation of development and peace building policies in Somalia. This situation opens up different spaces for the diaspora to have a role in Somalia. It is useful to analyze these with an interdisciplinary approach both in Somalia and outside.